Design of C band Bandpass Filter using Fractal based Symmetrical Ring Resonator - Sowjanya, A.; Vakula, D. (Advanced Electromagnetics, 2022)
Symmetrical ring resonator metamaterial along with fractal boundary is proposed for Band Pass Filter (BPF) design in this paper. A combination of symmetrical ring resonators and vias is used for designing a bandpass filter. Bandpass filter with low insertion loss, better fractional bandwidth even at higher frequencies is achieved by using moore fractal applied symmetrical ring metamaterial resonators along the microstrip transmission line. The operating frequency range of the simulated filter is in the C-band between 5.47 GHz - 6 GHz having fractional bandwidth (FBW) of 9.25% and with a minimum insertion loss of 1.2 dB. Application of moore fractal to the above implementation improved the bandwidth of the filter. Fractal applied symmetrical ring resonator simulated filter operates in the C-band between 7.15 GHz - 8.15 GHz having FBW of 13%, with a minimum insertion loss of 1 dB. The proposed filter is simulated, fabricated and S-parameters are measured using network analyzer N5222A. S-parameters results of fractal applied symmetrical ring resonator filter realized from simulations match closely with those from measurements results performed on prototypes but with a small shift in a frequency range. The measured filter operates in 6.95 GHz - 7.8 GHz having FBW of 11.5%, with a minimum insertion loss of 0.4 dB.